PENERAPAN ALAT CUCI TANGAN SEMI OTOMATIS DAN ERGONOMIS PADA PASAR BANDA AIA DI KECAMATAN KOTO TANGAH, PADANG - Irriwad Putri; Mohammad Agita Tjandra; Renny Eka Putri (LPPM Universitas Andalas, 2021)
Hand washing is the most important thing because it is simple and most influential in maintaining health caused by infectious diseases. Washing hands should use clean water and be free from germs. Hand washing in public handwashing stations must be carried out carefully because physical contact between users and faucets or soap dispensers can cause disease transmission or epidemics between users. Therefore, ergonomic and semi-automatic handwashing tools are made to reduce physical contact between users and these tools. The existence of the market in everyday life is essential for the community in meeting their daily needs. This activity aims to design, manufacture, and carry out the method of introducing handwashing tools. This service activity took place at the Banda Aia Market, Pasie Nan Tigo Village, Koto Tangah District, Padang City. This market is located in Pasie Nan Tigo (PNT) Village, Koto Tangah District, Padang City, the only market in Pasie Nan Tigo Village. The results obtained from this activity are (1) the Banda Aia market community is greatly helped by this hand washing tool, (2) the market community is more interested in washing their hands because they are not worried about contact with the hand washing place, (3) The public gets information about health care methods during the COVID-19 pandemic through health posters affixed to handwashing tools. From the implementation of this activity, it can be seen that awareness in washing hands after activities in the community is not only influenced by awareness alone, but the right tool to increase awareness becomes a habit.